2013
DOI: 10.1021/ct400423u
|View full text |Cite
|
Sign up to set email alerts
|

Geometries and Vertical Excitation Energies in Retinal Analogues Resolved at the CASPT2 Level of Theory: Critical Assessment of the Performance of CASSCF, CC2, and DFT Methods

Abstract: A systematic investigation of structural properties and vertical excitation energies of a series of structurally modified 11-cis-retinal chromophores in vacuo was performed by means of multiconfigurational second-order perturbation theory (CASPT2). CASPT2-based geometries agree reasonably well with Møller-Plesset second-order perturbation theory (MP2), local second-order approximate coupled cluster singles and doubles (LCC2), and density functional theory (DFT) geometries, while the complete active space self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 60 publications
8
62
0
Order By: Relevance
“…Biological systems containing conjugated CC bonds are also sensitive to light. Theoretical modeling of simplified systems sensitive to light has been reported recently by Andruniow and coworkers . The degree of electron delocalization in such molecular systems is reflected by a parameter called bond length alternation (BLA).…”
Section: Introductionmentioning
confidence: 99%
“…Biological systems containing conjugated CC bonds are also sensitive to light. Theoretical modeling of simplified systems sensitive to light has been reported recently by Andruniow and coworkers . The degree of electron delocalization in such molecular systems is reflected by a parameter called bond length alternation (BLA).…”
Section: Introductionmentioning
confidence: 99%
“…† All (de)methylated chromophore models have a spiral-like structure with a negative (counterclockwise) helicity, alike native 11-cis-RPSB. 43 It is evident from Fig. Bond lengths are decreased by 0.01-0.025 Å (0.01-0.015 Å at B3LYP), and dihedral angles are changed by up to 281 (up to 181 at B3LYP).…”
Section: Dark State Rhodopsinmentioning
confidence: 88%
“…52 Here we focus on the description of the Franck-Condon (FC) structure of the native Rh and its analogues with a modified RPSB chromophore. It has been previously found that CASSCF method overestimates the difference in single and double bond lengths in comparison to accurate Multi-Reference Configuration Interaction (MRCI) 66 and CASPT2 41,43,67,68 methods. 3 and 4, and in Tables S1-S4 in the ESI.…”
Section: Dark State Rhodopsinmentioning
confidence: 99%
See 2 more Smart Citations